2013
DOI: 10.1111/ajco.12074
|View full text |Cite
|
Sign up to set email alerts
|

Oral cyclophosphamide in recurrent ovarian cancer

Abstract: Single agent oral cyclophosphamide is active and well tolerated in recurrent ovarian cancer. Further investigation of oral cyclophosphamide in patients with platinum-sensitive and platinum-resistant disease is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…[913] In our study oral etoposide therapy was less tolerated with overall response rate of 16.6% (partial response) which was similar to other similar to other studies. [1011] In our study, no complete response was noted in the oral etoposide group.…”
Section: Discussionsupporting
confidence: 89%
“…[913] In our study oral etoposide therapy was less tolerated with overall response rate of 16.6% (partial response) which was similar to other similar to other studies. [1011] In our study, no complete response was noted in the oral etoposide group.…”
Section: Discussionsupporting
confidence: 89%
“…This profile of toxicity thus appears more favorable compared to previously reported experiences with MOC which, nonetheless, utilized slightly higher doses of the drug, i.e. 50–150 mg daily [ 13 ], or 50 mg twice a day for 3 weeks with a 1-week break [ 15 ], or 50–150 mg d1-14, every 4 weeks [ 16 ]. This observation, together with the recognized anti-angiogenic activity of MOC have provided the rationale for its combination with bevacizumab in retrospective as well as prospective studies which showed values of median PFS (range = 3.0-7.2 months) [ 29 31 ] comparable to our and previous results [ 16 ].…”
Section: Discussionmentioning
confidence: 88%
“…This consideration, together with the use of response evaluation criteria completely different from the current standard, intuitively precluded any reliable comparison with our results. A more recent feasibility study including 14 ROC patients documented an ORR to MOC of 7.1%, while a retrospective review of a similar patient setting reported a 44% response rate [ 16 ]; nonetheless, the reliability of these data are heavily impaired by the very small sample series [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that OMC has anti-tumor activity by itself in ovarian cancer [7]. The main primary target of OMC is thought to be the tumor's neovasculature.…”
mentioning
confidence: 99%